Diversity of Arbuscular Mycorrhizal Fungi in the Rhizosphere of Solaris and Regent Grapevine Plants Treated with Bioproducts - Sas-Paszt, L.; GÅ‚uszek, S.; Derkowska, E.; Sumorok, B.; Lisek, J.; TrzciÅ„ski, P.; Lisek, A.; FrÄ…c, M.; Sitarek, M.; PrzybyÅ‚, M.; et al. (South African Journal of Enology and Viticulture, 2020)
The aim of this study was to identify the spores of arbuscular mycorrhizal fungi (AMF) in the rhizosphere of Solaris and Regent grapevine plants grafted onto SO4 rootstock and treated with bioproducts. The bioproducts Ausuma, Bioilsa, manure and BF Ekomix were tested and applied on their own, or combined with standard mineral fertilisation (NPK). The applied bioproducts contributed to an increase in the number of species of mycorrhizal fungi in the rhizosphere soil of the grapevines. The most frequently occurring AMF species was Claroideoglomus claroideum. Biopreparation BF Ekomix was a promising agent for increasing the number of AMF spores in the rhizosphere of Regent grapevines. In the rhizosphere of Solaris, a positive influence on the number of spores occurred after the application of Bioilsa.